Generalized Stability of Euler-Lagrange Quadratic Functional Equation - Hark-Mahn Kim; Min-Young Kim (Abstract and Applied Analysis)
The main goal of this paper is the investigation of the general solution and the generalized Hyers-Ulam stability theorem of the following Euler-Lagrange type quadratic functional equation f(ax+by)+af(x-by)=(a+1)b2f(y)+a(a+1)f(x), in (β,p)-Banach space, where a,b are fixed rational numbers such that a≠-1,0 and b≠0.